Ways of improvement railway transport in overpass economic crisis conditions - Deineka, O. H.; Bozhok, A. R. (Science and Transport Progress, 2011)
In the article a problem of adapting the railway transport to market requirements is presented and the ways of improving its competitiveness are investigated. Some measures and reserves of improving the operation efficiency for the railway transport are offered.